The Potential Effect of Different Doses of Ionizing Radiation on Genes and Disease - Lin, Cheng-Chia (Dose Response, 2019)
AIM: The chromosomal aberrations induced by radiation appear about nonrandomly distributed across the whole genome. Previous studies have shown that chromosomes with high DNA content are less frequently involved in the formation of symmetrical translocations and dicentric chromosomes than expected, whereas smaller chromosomes are more frequently involved. We hypothesized that these translocation regions are linked to radiation sensitivity. MATERIALS AND METHODS: We investigated the frequencies of chromosome translocations induced by radiation exposure and adjusted the results according to chromosome length. We specifically analyzed whole blood samples from 3 participants. The samples were irradiated using (60)Co at doses of 0.5, 1, 2.5, and 5 Gy. Traditional Giemsa-trypsin-Wright band staining was performed to identify the translocations in the chromosomes, and results were compared with microarray data generated in our previous study. RESULTS: Our analysis indicated that chromosomes 9q were the most sensitive to translocations after various doses of radiation, and such translocations occurred in the euchromatin region. Chromosomes 1, 9, 15, and 17 were more sensitive to radiation doses of 0.5 Gy. This observation could be useful when selecting sensitive reference chromosomes in the low-dose region. The results of expression profiling analysis for radiation-sensitive regions were similar to those of chromosome translocation analysis. CONCLUSION: This study shows that some chromosomes or genomic regions are more sensitive to alteration by radiation exposure.